1997
DOI: 10.1111/j.1440-1754.1997.tb01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal factors as predictors of child behaviour at 5 years

Abstract: Objective:The Mater University Study of Pregnancy (MUSP) is a prospective cohort study of 8556 mothers enrolled in early pregnancy. The relationship of obstetric and perinatal factors, maternal lifestyle, age and gender of the child, and social disadvantage were examined as predictors of child behaviour in 5005 children completing a modified child behaviour checklist at 5 years. This checklist contained three independent groups of behaviour: externalizing, internalizing and SAT (social, attentional and thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
(25 reference statements)
3
24
0
Order By: Relevance
“…Male gender has been found to be associated with increased prevalence in undercontrolled behaviour (2,12,13); this was also confirmed in our study. Male gender was also found to be associated with increased prevalence of anxious behaviour.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Male gender has been found to be associated with increased prevalence in undercontrolled behaviour (2,12,13); this was also confirmed in our study. Male gender was also found to be associated with increased prevalence of anxious behaviour.…”
Section: Discussionsupporting
confidence: 90%
“…The male gender is known to be associated with a higher prevalence of undercontrolled behaviour, attention deficit disorder and conduct disorder (2,12,13). The female gender is more inclined toward overcontrolled behaviour (2).…”
mentioning
confidence: 98%
“…Boys had more Externalizing (Delinquent) and Attention problems compared with girls. This is in agreement with the observations of O'Callaghan et al 38 Other factors that were predictors of childhood behavior in the adjusted analysis were changes in the child's custody status and higher child lead levels. Maternal/prenatal factors that were associated with problem child behavior included maternal smoking during pregnancy, lower maternal education, and lower scores on the modified HOME inventory.…”
Section: Discussionsupporting
confidence: 82%
“…As reported earlier, most common epidemiologic obstetric and perinatal risk factors were not independent predictors of behavior problems in children at 6 years. 37,38 Child gender significantly affected behavior scores. Boys had more Externalizing (Delinquent) and Attention problems compared with girls.…”
Section: Discussionmentioning
confidence: 99%
“…Important information can also be gleaned from population-based studies that have identified early-life risk factors that predict inattention/hyperactivity or externalizing behaviour rather than a diagnosis of ADHD. These studies have implicated factors such as antenatal anxiety, maternal/ paternal postnatal depression, smoking during pregnancy, stress during pregnancy, number of antenatal visits, male gender, maternal age and education and family income O'Callaghan et al 1997;O'Connor et al 2002;Ramchandani et al 2005;Rodriguez and Bohlin 2005;Romano et al 2006;Williams et al 1998).…”
Section: Examining Early Life Risk Factors For Adhd Within Populationmentioning
confidence: 99%